Islamic banking during the financial crisis of 2007 - Derbali, Abdelkader (Serbian Journal of Management, 2014)
The purpose of this paper is to initially contribute the literature linking the global financial crisis and performance of Islamic banks. Thus, it is important for everyone's future that it was study the current crisis in order to develop sustainable financial practices and in quest of a new business model based on sharing the profit and loss. This sustainable financial practice is based on non-interest-based transactions but profit and loss sharing should be in practice at the financial system. In this paper, it was test the performance of the Islamic banks in a period of crisis. It was use a sample of 29 Islamic banks from 7 countries and from a period of study of 7 years (2006-2012). According to the empirical results, it was concluding that the Islamic banks do not affected by the financial crisis of 2007.